Spontaneous breathing approach in mild congenital diaphragmatic hernia: A resuscitation algorithm - Horn-Oudshoorn, Emily J. J.; Knol, Ronny; Cochius-den Otter, Suzan C. M.; te Pas, Arjan B.; Hooper, Stuart B.; Roberts, Calum T.; Rafat, Neysan; Schaible, Thomas; de Boode, Willem P.; van der Lee, Robin; Debeer, Anne; Kipfmueller, Florian; et al. (Frontiers in Pediatrics, 2022)
Background: Infants with a congenital diaphragmatic hernia (CDH) and expected mild pulmonary hypoplasia have an estimated survival rate of 90%. Current guidelines for delivery room management do not consider the individual patient’s disease severity, but an individualized approach with spontaneous breathing instead of routine mechanical ventilation could be beneficial for the mildest cases. We developed a resuscitation algorithm for this individualized approach serving two purposes: improving the success rate by structuring the approach and providing a guideline for other centers. Methods: An initial protocol was discussed with all local stakeholders. Afterwards, the resulting protocol was refined using input from international experts. Results: Eligible CDH infants: left-sided defect, observed to expected lung-to-head ratio >50%, gestational age at birth ≥37.0 weeks, and no major associated structural or genetic abnormalities. To facilitate fetal-to-neonatal transition, we propose to start stabilisation with non-invasive respiratory support and to adjust this individually. Conclusions: Infants with mild CDH might benefit from an individualized approach for neonatal resuscitation. Herein, we present an algorithm that could serve as guidance for centers implementing this.